2009
DOI: 10.1007/s11104-009-0016-z
|View full text |Cite
|
Sign up to set email alerts
|

Botanical composition, production and nutrient status of an originally Lolium perenne-dominant cut grass sward receiving long-term manure applications

Abstract: fertilizer N in 2006, whereas about 100 m 3 ha −1 pig slurry were required to produce a similar amount of DM. The highest slurry application rate significantly influenced sward botanical composition without depressing DM yield. The principal invading species were creeping bent and meadow grasses (similar to findings at a previous assessment in 1981) except in the unamended control (which were common bent and Yorkshire fog). Perennial ryegrass remained a main species in plots receiving fertilizer (31 % annual D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 21 publications
3
19
0
Order By: Relevance
“…Contrary, Zechmeister et al (2003) reported meadows with > 90 kg N/ha/year differed in species richness significantly from those with lower levels of fertilizer application. Significant changes in plant species composition among treatments including cattle and pig slurries application found also Liu et al (2010). As expected, the cover of tall grasses positively responded to N application, similarly to Pavlů et al (2011b, Čámská and Skálová (2012) and Hejcman et al (2012).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Contrary, Zechmeister et al (2003) reported meadows with > 90 kg N/ha/year differed in species richness significantly from those with lower levels of fertilizer application. Significant changes in plant species composition among treatments including cattle and pig slurries application found also Liu et al (2010). As expected, the cover of tall grasses positively responded to N application, similarly to Pavlů et al (2011b, Čámská and Skálová (2012) and Hejcman et al (2012).…”
Section: Discussionsupporting
confidence: 69%
“…Liu et al 2010). The aim of this study was therefore to evaluate the effect of cattle slurry application ranging from 0 to 240 kg N/ha/year on plant species composition of Arrhenatherion grassland cut three times per year.…”
mentioning
confidence: 99%
“…Nitrogen application substantially decreased N concentration in the biomass from the D, E and F treatments compared with the control, although many researchers have recorded the opposite result, i.e., an increase in biomass N concentration with N application (Pelletier et al 2006;Pontes et al 2007;Aavola and Kärner 2008;Brum et al 2009;Liu et al 2010;Malhi et al 2010;Pan et al 2010). This can be explained in three possible ways.…”
Section: Concentration Of Elements In the Biomassmentioning
confidence: 98%
“…The long-term application of organic fertilizers resulted in the significant changes in the sward botanical composition also in the studies of Liu et al (2010). Elsaesser et al (2008) investigated the effects of different fertilization systems (organic and mineral fertilizers) on permanent grasslands and found that fertilization with slurry increased the proportions of grasses, whereas farmyard manure increased forbs; the proportion of legumes was increased by PK and by fertilization with slurry with lime.…”
Section: Functional Groupsmentioning
confidence: 99%
“…Cattle slurry, in particular, is a commonly used fertilizer in many countries, and its effect on grassland has been studied (e.g. Liu et al 2010;Lalor et al 2012;Duffková & Libichová 2013). …”
mentioning
confidence: 99%